How crop breeding programs can improve plant factories' business and environmental sustainability: Insights from a farm level analysis - Shuang Song; Edwin J.K. Ong; Adrian M.J. Lee; Fook Tim Chew (Sustainable Production and Consumption, 2024)

Sensitization to Airborne Fungal Allergens Associates with Asthma and Allergic Rhinitis Presentation and Severity in the Singaporean/Malaysian Population - Yang Yie Sio; Sze Lei Pang; Yee-How Say; Keng Foo Teh; Yi Ru Wong; Smyrna Moti Rawanan Shah; Kavita Reginald; Fook Tim Chew (Mycopathologia, 2021)
Fungal spores and conidia are the major components of total airspora in the tropical Asia environment, and their sensitization patterns are often associated with allergic diseases such as asthma, allergic rhinitis (AR), and atopic dermatitis. Hence, we recruited a cross-sectional cohort of 9223 Singapore/Malaysia Chinese adults and assessed their sensitization against Curvularia lunata allergen using the skin prick test approach. A subset of this cohort ( n = 254) was also screened for specific Immunoglobulin E (sIgE) titers against a panel of 11 fungal allergens. We found significant association of Curvularia lunata sensitization with the risk of asthma (OR = 1.66, 95% CI: 1.17–2.33 ; p = 0.00391) and AR (OR = 1.69, 95% CI: 1.18–2.41; p = 0.00396). Among asthmatic patients ( n = 1680), Curvularia lunata sensitization also increased frequencies of wheezing symptoms (OR = 1.81, 95% CI: 1.05–2.96; p = 0.0239), general practitioner/specialist visits (OR = 2.37, 95% CI: 1.13–4.61; p = 0.0157), and other asthma-related exacerbation events (OR = 2.14, 95% CI: 1.04–4.10; p = 0.0289). In our serum cohort, sensitization to Aspergillus spp. was the most common fungal sensitization, with 23.6% ( n = 60) had a class 3 and above sensitization (positive sensitization; sIgE titers of > 3.5 kU/L) against this allergen. Increasing sIgE titer against Aspergillus spp. was also correlated with increased AR risk and AR-related symptoms. In conclusion, our findings emphasize an important role of fungal sensitization in the manifestations of asthma and AR in the Southeast Asian Chinese population.

Female spider aggression is associated with genetic underpinnings of the nervous system and immune response to pathogens - Chia‐chen Chang; Heidi Connahs; Estella Cai Yu Tan; Y. Norma‐Rashid; Mrinalini; Daiqin Li; Fook Tim Chew (Molecular Ecology, 2020)
Identifying the genetic architecture underlying phenotypic variation in natural populations and assessing the consequences of polymorphisms for individual fitness are fundamental goals in evolutionary and molecular ecology. Consistent between‐individual differences in behaviour have been documented for a variety of taxa. Dissecting the genetic basis of such behavioural differences is however a challenging endeavour. The molecular underpinnings of natural variation in aggression remain elusive. Here, we used comparative gene expression (transcriptome analysis and RT–PCR), genetic association analysis and pharmacological experiments to gain insight into the genetic basis of aggression in wild‐caught jumping spiders ( Portia labiata ). We show that spider aggression is associated with a putative viral infection response gene, BTB/POZ domain‐containing protein 17 (BTBDH), in addition to a putative serotonin receptor 1A (5‐HT1A) gene. Spider aggression varies with virus loads, and BTBDH is upregulated in docile spiders and exhibits a genetic variant associated with aggression. We also identify a putative serotonin receptor 5‐HT1A gene upregulated in docile P. labiata . Individuals that have been treated with serotonin become less aggressive, but individuals treated with a nonselective serotonin receptor antagonist (methiothepin) also reduce aggression. Further, we identify the genetic variants in the 5‐HT1A gene that are associated with individual variation in aggression. We therefore conclude that co‐evolution of the immune and nervous systems may have shaped the between‐individual variation in aggression in natural populations of jumping spiders.

Fern spore and pollen airspora profile of Singapore - Tan Ching Ong; Soo Hwee Lim; Xiaowei Chen; Siti Dahlia Mohd Dali; Hugh Tiang Wah Tan; Bee Wah Lee; Fook Tim Chew (Aerobiologia, 2012)